2010
DOI: 10.1016/j.pmrj.2010.04.020
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional Factors That Influence Change in Bone Density and Stress Fracture Risk Among Young Female Cross‐Country Runners

Abstract: In young female runners, low-fat dairy products and the major nutrients in milk (calcium, vitamin D, and protein) were associated with greater bone gains and a lower stress fracture rate. Potassium intake was also associated with greater gains in hip and whole-body BMD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
102
4
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 144 publications
(112 citation statements)
references
References 79 publications
(112 reference statements)
3
102
4
3
Order By: Relevance
“…These studies, however, suggest that high physical activity can have a more determining role in the development and maintenance of normal bone mass than high calcium intake with the diet. Simultaneously, other studies have shown a positive association with increased calcium intake from the diet with improved bone density and reduction of fractures in runners (Myburgh, 1999;Nieves et al, 2002). Myburgh et al (1999) conducted a clinical-control study which evaluated the risk of stress fractures in long-distance runners, depending on the content of calcium in their diet.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These studies, however, suggest that high physical activity can have a more determining role in the development and maintenance of normal bone mass than high calcium intake with the diet. Simultaneously, other studies have shown a positive association with increased calcium intake from the diet with improved bone density and reduction of fractures in runners (Myburgh, 1999;Nieves et al, 2002). Myburgh et al (1999) conducted a clinical-control study which evaluated the risk of stress fractures in long-distance runners, depending on the content of calcium in their diet.…”
Section: Discussionmentioning
confidence: 99%
“…Bioavailability of iron from vegetable products is greatly increased by the dietary components such as vitamin C, fructo-oligosaccharides or resistant starch. Many sportsmen use supplementation to compensate for the iron deficiencies (Alaunyte et al, 2015;Nieves et al, 2002). It should be noted, however, that uncontrolled iron supplementation especially for amateur sportsmen is inadvisable.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Kalsiyum ve D vitamini, kemik sağlığını korumak ve geliştirmek için gerekli beslenmenin önemli iki bileşeni olarak kabul edilmektedir. Kadın sporcular ve askerlerde yapılan çalışmalarda elde edilen bulgular günde 1500 mg'dan fazla kalsiyum tüketenlerde stres kırığı riskinin daha az olduğunu gös--termektedir (11,12). Myburgh ve ark.…”
unclassified
“…Nieves ve ark. 18--26 yaş aralığında--ki yarışmacı kadın mesafe koşucularında yaptıkları prospektif çalışmada kalsiyum, D vitamini ve protein alımındaki artışın kemik mineral yoğunluğundaki artış ve stres kırıklarından korunma ile ilişkili ol--duğunu göstermişlerdir (12). Günde 800 mg'dan az kalsiyum tüketen kadınlarda 800--1500 mg arası kalsiyum tüketenlere oranla iki kat, 1500 mg'dan fazla kalsiyum tüketen kadınlara oranla da yaklaşık altı kat daha fazla kırık riski bulunmuştur.…”
unclassified